Treatment of UTIs Due to Klebsiella pneumoniae Carbapenemase-Producers: How to Use New Antibiotic Drugs? A Narrative Review - Caroline Chapelle (MDPI AG, 2021)
Background: K. pneumoniae is one of the bacteria most frequently causing health care-associated urinary tract infections, and increasingly incriminating Klebsiella pneumoniae carbapenemase producers (KPCp). Most infections caused by KPCp are nosocomial and might cause serious issues, even leading to death in half of the reported cases. Our aim was to identify the best strategy, based on available scientific data, for the use of new antibiotic treatments to manage KPCp UTIs. Methods: this narrative review of the literature was performed according to the criteria of preferred reporting items for systematic review and meta-analyses statement (PRISMA) (2020). Results and Conclusions: KPCp-UTIs are a real challenge for physicians. While cefiderocol, meropenem-vaborbactam, ceftazidim-avibactam, and imipenem-relebactam represent a major step forward in the treatment of these UTIs, no guidelines are currently available, in view of choosing the most appropriate treatment, in each specific case.